Effects of tissue type and season on the detection of regulated sugarcane viruses by high throughput sequencing - Stephen Bolus; Kate Wathen-Dunn; Samuel C. Grinstead; Xiaojun Hu; Martha Malapi; Dimitre Mollov (CABI Agriculture and Bioscience)
Abstract High throughput sequencing (HTS) can supplement and may replace diagnostic tests for plant pathogens. However, the methodology and processing of HTS data must first be optimized and standardized to ensure the sensitivity and repeatability of the results. Importation of sugarcane into the United States is highly regulated, and sugarcane plants are subjected to strict quarantine measures and diagnostic testing, especially for the presence of certain viruses of regulatory concern. Here, we tested whether HTS could reliably detect four RNA and three DNA sugarcane viruses over three seasons (fall, winter, and spring) and in three tissue types (root, stem, and leaves). Using HTS on ribosomal depleted total RNA samples, we reliably detected RNA viruses in all tissue types and across all seasons, but we failed to confidently detect DNA viruses in some samples. We recommend that future optimization be employed to ensure the robust and reliable detection of all regulated sugarcane viruses by HTS.